2017
DOI: 10.5004/dwt.2017.20290
|View full text |Cite
|
Sign up to set email alerts
|

Pollution parameters and identification of performance indicators for wastewater treatment plant of Medea (Algeria)

Abstract: The sanitation system in Algeria requires a mastery of the functioning of the collection network and treatment using performance indicators that identify gaps and to develop solutions for better waste-water management. This work aims to identify the performance indicators that are chosen on the basis of the problems often encountered. The referred performances concern the problems related to clear parasites waters and some that highlight the phenomena of sedimentation-erosion in the net-work of Medea city. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
1
3
1
Order By: Relevance
“…A significant correlation was observed between dysfunction parameters. This funding's was also mentioned by other authors (Karefa et al, 2017;Rekrak & Fellah, 2020;Salama et al, 2020). They demonstrated the relationship between the Dilute Sludge Volume Index (DSVI) and the density of filamentous bacteria (FI).…”
Section: Discussionsupporting
confidence: 80%
“…A significant correlation was observed between dysfunction parameters. This funding's was also mentioned by other authors (Karefa et al, 2017;Rekrak & Fellah, 2020;Salama et al, 2020). They demonstrated the relationship between the Dilute Sludge Volume Index (DSVI) and the density of filamentous bacteria (FI).…”
Section: Discussionsupporting
confidence: 80%
“…Our findings show the BOD 5 levels in the treated water from the Ain Sefra WWTP are comparable or lower than other studies in Algeria. For example, a study conducted in Medea's WWTP reported BOD 5 levels reaching a maximum value of 352.33 mg/L in the treated effluent, which exceeds our findings [53]. WWTPs worldwide typically report BOD 5 levels between 10-50 mg/L [54][55][56].…”
Section: Discussioncontrasting
confidence: 66%
“…The COD/BOD 5 ratio of raw domestic wastewaters has usually been reported within the range of 1.25 and 2.50 [38]. Wastewater having the COD/BOD 5 ratio below 2 can easily be biodegraded while the biodegradability of sewage is susceptible to be limited if the COD/BOD 5 > 3 [48][49][50][51]. With the mean COD/BOD 5 of 2.23 for the DWWTP, Figure 9a suggests that the DWWTP performance could be sustained for a quite appreciable range of COD/BOD 5 ratio.…”
Section: Influence Of Influent Wastewater Cod Fractioning and Nitrogementioning
confidence: 99%
“…Low BOD 5 /TN ratio in an influent leads to a quick carbon deficit and an uneven nitrification and denitrification process due to the competition between denitrifying bacteria and other heterotrophs substrate [20,52]. On the other hand, with a lower COD/TKN ratio, ASPs could be in more carbon-limited conditions for some domestic wastewaters, which might be inadequate to attain complete denitrification [48]. However, this is not the case for DWWTP having an average value of 7.89, which is manifested in the high denitrification of by the DWWTP.…”
Section: Influence Of Influent Wastewater Cod Fractioning and Nitrogementioning
confidence: 99%